ISTILAH NEGARA HUKUM DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA - Manan Sailan (Faculty of Law, Universitas Diponegoro, 2011)
State Law is a dream almost every sovereign state. Because the conception of law implies the state government must be executed under the law. Also means that government must be held for public purposes reather than for the benefit of certain individuals or groups. Thus, state law is constitutional state based on law not based on sheer power. Kata kunci: Negara Hukum, Sistem Ketatanegaraan Rl